Global retirement and pensions system development - Nik Hazimi, Mohammed Foziah; Puspa Liza, Ghazali; Alias, A.; Sukonob, .; Bon, A.T. (2021)
This paper focuses on the development trends of retirement and pension system over the world. It begins with the dated back on the first establishment of the system, continued with the chronological of its entire system. Then the paper highlights the contributory and non-contributory pension system in which classified into several perspectives. Furthermore, the discussion has brought the attention to the two basic models of retirement system known as defined-benefit and defined contribution. At the end, this paper concludes with the challenges and future directions of the retirement system which can give a huge impact to the government and authorities to have a better preparation towards on an ageing nation.